Manufacturing of a Transdermal Patch in 3D Printing - Isabella Villota; Paulo César Calvo; Oscar Iván Campo; Luis Jesús Villarreal-Gómez; Faruk Fonthal (Micromachines, 2022)
Diabetes mellitus is an endocrine disorder that affects glucose metabolism, making the body unable to effectively use the insulin it produces. Transdermal drug delivery (TDD) has attracted strong interest from researchers, as it allows minimally invasive and painless insulin administration, showing advantages over conventional delivery methods. Systems composed of microneedles (MNs) assembled in a transdermal patch provide a unique route of administration, which is innovative with promising results. This paper presents the design of a transdermal patch composed of 25 microneedles manufactured with 3D printing by stereolithography with a class 1 biocompatible resin and a printing angle of 0°. Finite element analysis with ANSYS software is used to obtain the mechanical behavior of the microneedle (MN). The values obtained through the analysis were: a Von Misses stress of 18.057 MPa, a maximum deformation of <semantics>2.179×10−3</semantics>, and a safety factor of 4. Following this, through a flow simulation, we find that a pressure of 1.084 Pa and a fluid velocity of 4.800 <semantics>ms</semantics> were necessary to ensure a volumetric flow magnitude of <semantics>4.447×10−5cm3s</semantics>. Furthermore, the parameters found in this work are of great importance for the future implementation of a transdermal drug delivery device.